PENGARUH MEDIA FLASH CARD TERHADAP KEMAMPUAN MENGENAL KOSA KATA ANAK USIA 3-4 TAHUN DI PAUD MUTHIA ISLAMIC SCHOOL KAYU AGUNG - Nina Kholifah; Amir Hamzah; Kurnia Dewi (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine flash card media on the ability to recognize vocabulary in children aged 3-4 years at PAUD Muthia Islamic School Kayuagung. This type of research is quantitative experimental Design One Group Pre-test Post-test (one class). The research sample used in this research was group a at PAUD Muthia Islamic School Kayuagung, totaling 12 children, namely 7 boys and 5 girls. The sampling technique is carried out using Sample Random Sampling or the children are called one by one to come to the front of the class to bring flash card media that has been prepared by the teacher. The method for collecting data uses observation tests and documentation with data analysis using normality tests, homogeneity tests and hypothesis tests. The results of the research and discussion mean the average pre-test score that did not use treatment was 68, while the average post-test score using flash card media or treatment was 88. It can be seen that there is an influence when not using the media and after using the flash card media. These findings are strengthened based on the results of the hypothesis test, namely rtable, it can be seen that because to has been obtained = 9.161 while tt = 2.07387. So t0 is greater than tt, both at the 5% significance level with details of 9.161>2.07387 then the significance is 0.02<0.05= significant and Ha is accepted which means there is a significant influence between flash card media on the ability to recognize vocabulary. said to children aged 3-4 years at PAUD Muthia Islamic School Kayuagung.